Indicating Significance of Current Research: Pedagogical Implications of a Genre Analysis for Dissertation Writing - Jason Miin-Hwa Lim (2008)
Effectiveness of supervising undergraduate and postgraduate students in dissertation writing hinges largely on a range of factors comprising not merely a supervisor’s competence in an area of specialisation but also the supervisor’s language awareness required for guiding a candidate through a difficult process of writing the dissertation itself. Using a corpus of management research articles and the methods for analysing the research genre, this paper examines how experienced writers use various rhetorical and linguistic strategies to highlight the significance of their research in the terminal portions of their papers. The findings of this study have important implications for the teaching of English for research purposes (ERP) particularly as they indicate how second language learners may be taught to highlight the strengths of their studies based on the findings reported. I will also discuss the extent to which supervisors and instructors can help students augment the acceptability of a dissertation by developing teaching materials that introduce various schematic and linguistic strategies intended to highlight the strengths of a candidate’s research findings.